Investigation of the relationship of the use of the cellular and/or smartphone appliance with osteomioarticular lesions of the cervical spine and hand - Eduardo Lopes Marques Xavier; Djavan Gomes Leite; Weslley Barbosa Sales; Leonildo Santos do Nascimento Júnior (Open Journal of Pain Medicine - Peertechz Publications, 2023)
Introduction: Considering that the cell phone and/or smartphones had become part of the human being and thus brought problems to people's health.  Objective: To investigate the existing relationship between the use of mobile telephone devices and the health problems of the user, focusing on musculoskeletal injuries of the cervical spine and hand and as hypotheses had the existence or not of this relationship.  Methodology: A field study, cross-sectional, with a quantitative approach, of the descriptive type, was carried out in March and April 2019 with academics from the Physiotherapy course at Centro Universitário de João Pessoa- Unipê. Data collection was carried out through a questionnaire that explored questions related to socio-demographic data, the reasons why the devices are used, the quantification of hours of use per day and the postures adopted, among others.  Discussions: The data were analyzed and described through tabulation in Microsoft Excel version 2016 through simple descriptive statistics and in that same program, graphs and tables were constructed for a better display of the results that were confronted with the scientific literature. The sample was mostly female, single, brown, with income between one and five minimum wages and right-handed.  Conclusion: There are reasons for this relationship to exist and that the problems arising from this interaction continue to grow since users, despite feeling pain, heaviness, numbness and tingling, among others, do not abandon their devices and because it is a theme that involves the world, it needs to be special attention from the scientific community.